Are We Recording? Putting Embayment Speedometry to the Test Using High Pressure‐Temperature Decompression Experiments - Behnaz Hosseini; Madison L. Myers; James M. Watkins; Megan A. Harris (Geochemistry, Geophysics, Geosystems, 2023)
Abstract Despite its increasing application to estimate magma decompression rates for explosive eruptions, the embayment speedometer has long awaited critical experimental evaluation. We present the first experimental results on the fidelity of natural quartz‐hosted embayments in rhyolitic systems as recorders of magma decompression. We conducted two high pressure‐temperature isobaric equilibrium experiments and 13 constant‐rate, continuous isothermal decompression experiments in a cold‐seal pressure vessel where we imposed rates from 0.005 to 0.05 MPa s−1 in both H2O‐saturated and mixed‐volatile (H2O + CO2)‐saturated systems. In both equilibrium experiments, we successfully re‐equilibrated embayment melt to new fluid compositions at 780°C and 150 MPa, confirming the ability of embayments to respond to and record changing environmental conditions. Of the 32 glassy embayments recovered, seven met the criteria previously established for successful geospeedometry and were thus analyzed for their volatile (H2O ± CO2) concentrations, with each producing a good model fit and recovering close to the imposed decompression rate. In one H2O‐saturated experiment, modeling H2O concentration gradients in embayments from three separate crystals resulted in best‐fit decompression rates ranging from 0.012 to 0.021 MPa s−1, in close agreement with the imposed rate (0.015 MPa s−1) and attesting to the reproducibility of the technique. For mixed‐volatile experiments, we found that a slightly variable starting fluid composition (2.4–3.5 wt.% H2O at 150 MPa) resulted in good fits to both H2O + CO2 profiles. Overall our experiments provide confidence that the embayment is a robust recorder of constant‐rate, continuous decompression, with the model successfully extracting experimental conditions from profiles representing nearly an order of magnitude variation (0.008–0.05 MPa s−1) in decompression rate.